Antifeeding and Oviposition Deterrent Effect of Ludwigia spp. (Onagraceae) against Plutella xylostella (Lepidoptera: Plutellidae) - Eliana Aparecida Ferreira; Eduardo Carvalho Faca; Silvana Aparecida de Souza; Claudemir Antonio Garcia Fioratti; Juliana Rosa Carrijo Mauad; Claudia Andrea Lima Cardoso; Munir Mauad; Rosilda Mara Mussury (Plants, 2022)
Plants produce a wide variety of bioactive compounds with insecticidal properties, such as secondary metabolites capable of interfering with the nutrition and reproduction of pest species such as Plutella xylostella. Thus, the objective of this study was to evaluate the effects of aqueous and ethanolic extracts of Ludwigia spp. (Onagraceae) on the feeding and oviposition of P. xylostella. Choice bioassays were performed using aqueous and ethanolic extracts. The aqueous extract of L. tomentosa resulted in an approximately 81% reduction in larval feeding compared to that in the control, with an antifeedant index (AI) of 52%. The aqueous and ethanolic extract of L. nervosa acted by stimulating larval feeding. The oviposition was significantly reduced in the kale leaves treated with aqueous and ethanolic extracts of Ludwigia spp. The aqueous extracts promoted an average 90% reduction in oviposition when compared to that in the control, and an oviposition deterrent index (ODI) above 61% was classified as an oviposition deterrent. In addition, ethanolic extracts affected 81% of oviposition, with an ODI above 41%. Bioassays should be performed to clarify the use of aqueous and ethanolic extracts of L. nervosa as they acted as phagostimulants in the feeding tests and as deterrents in the oviposition tests. The phenolic compounds—flavonoids, condensed tannins, and alkaloids—were more abundant in L. nervosa, L. tomentosa, L. sericea, and L. longifolia. The extracts of L. longifolia and L. tomentosa showed the best results, interfering with the host choice for feeding and oviposition in P. xylostella and representing an alternative for the control of diamondback moths.